Pelatihan UMKM Limbah Nanas Pewarna Alami Kain Jumputan Peluang Bisnis Kearifan Lokal Masyarakat Pinggiran Era Covid-19 - Lesi Hartati; Asmawati Asmawati; Rum Hendarmin; Lili Syafitri (STAI Auliaurrasyidin Tembilahan, 2021)
The community is full of pressure due to the sudden emergence of the covid-19 outbreak which has an impact on MSME businesses, so the idea of ​​​​using pineapple waste is unique. Jumputan is a handicraft made by picking (picking up with your fingers) certain parts of the fabric, then producing a motif according to the pattern drawn from the dyeing process of natural dyes and textile dyes from tightly tied fabrics. Pineapple waste which is not useful for indigenous people into natural dyes to make fabric colors. Pineapple waste is often immediately thrown away, even though if it is used as an interesting work, it will be beneficial for the wider community. By turning Pineapple waste into a beautiful work of art, the price is high. Many people are interested in having it. Besides being able to be reused, the results of used Pineapple Waste craft products can be a business opportunity. Pineapple is usually made. Food jam to be eaten with bread. This time, pineapple waste is a light and easy to use material, even using and playing with Pineapple waste can produce interesting works that are expensive. Not a few people still think that Pineapple has a fragile character and easily rots, especially not durable, this time it was used for natural dyes for fabric jumputans